A lei 14.181/2021 e a prevenção ao superendividamento de pessoas idosas como garantia do mínimo existencial - Monte, Luciana Budoia (2023)
The Constitution of the Federative Republic of Brazil welcomed the capitalist mode of production, although rejecting predatory capitalism by founding itself over the human dignity and the objectives of building a free, fair, and solidary society. In addition, it chose consumer protection as a principle of the economic order and demanded the drafting of a law to protect this group and reserved special protection for the elderly. However, elderly consumers are victims of harassment and pressure from the financial industry that, using abusive methods, convinces them to take out credit without having the dimension of the debt and the risks of over-indebtedness. Harassment within the family itself contributes to the acquisition of debt by the elderly. The poor income, low literacy, and lack of financial education of a large part of the Brazilian elderly population accentuate their vulnerability. The possibility of contracting withholding credit on social security benefits emerges as a very low-risk business for creditors but a considerable risk for the elderly, who end up compromising their existence minimum. On the other side, the National Institute of Social Security, which should supervise the firms that offer this product, does not fulfil its task. In addition, the Superior Courts of the Judicial power tend to enforce the principle of autonomy of will instead of the human dignity and the guarantee of the existence minimum. In this scenario, aggravated by the growing indebtedness of the Brazilian population, Federal Law 14.181/2021 emerges as a fundamental tool against over-indebtedness, establishing responsible credit concession and financial education as pillars in preventing this phenomenon and reiterating the need for special protection for the elderly. Its effectiveness, however, will depend on a change in the Judicial power perception regarding over-indebted people, on the active surveillance and control over credit institutions and on a new public policy aimed at the financial education of the elderly. This study bases itself on the literature review, supported by statistics and qualitative research to analyze the aggravated risk of over-indebtedness of the elderly, uses the inductive method to verify judicial precedents to describe the inclinations of the Superior Courts, and the hypothetico-deductive method to formulate suggestions to materialize the protection of this hypervulnerable group to prevent their over-indebtedness.